Quantum dynamics of a Josephson junction driven cavity mode system in the presence of voltage bias noise - Wang, Hui; Blencowe, M.P.; Armour, A.D.; Rimberg, A.J. (American Physical Society, 2017)
We give a semiclassical analysis of the average photon number as well as photon number variance (Fano factor F) for a Josephson junction (JJ) embedded microwave cavity system, where the JJ is subject to a fluctuating (i.e., noisy) bias voltage with finite dc average. Through the ac Josephson effect, the dc voltage bias drives the effectively nonlinear microwave cavity mode into an amplitude squeezed state (F <1), as has been established previously [Armour et al., Phys. Rev. Lett. 111, 247001 (2013)], but bias noise acts to degrade this squeezing. We find that the sensitivity of the Fano factor to bias voltage noise depends qualitatively on which stable fixed point regime the system is in for the corresponding classical nonlinear steady-state dynamics. Furthermore, we show that the impact of voltage bias noise is most significant when the cavity is excited to states with large average photon number.